Shipwrecked in Paradise : Cleopatra's Barge in Hawai'i - Johnston, Paul Forsythe, 1950- (Book collections on Project MUSE., 2015)
The first oceangoing yacht ever built in America, Cleopatra's Barge, endured many incarnations over her eight-year life, from Mediterranean pleasure cruiser to a Hawaiian king's personal yacht. The famed ship, at times also a Christian missionary transport, pirate ship, getaway vehicle, instrument of diplomacy, and racing yacht, wrecked on a reef in Hanalei Bay on April 6, 1824. Obtaining the first underwater archaeological permits ever issued by the state of Hawai'i, a team of divers from the Smithsonian Institution located, surveyed, and excavated the wrecked ship from 1995 to 2000. The 1,25.